IgG-Independent Co-aggregation of FcεRI and FcγRIIB Results in LYN- and SHIP1-Dependent Tyrosine Phosphorylation of FcγRIIB in Murine Bone Marrow-Derived Mast Cells - Gast, Mathias; Preisinger, Christian; Nimmerjahn, Falk; Huber, Michael (Frontiers in Immunology, 2018)
Activation of the high-affinity receptor for IgE (FcεRI) follows a bell-shaped dose-response curve. Upon supra-optimal stimulation, mast cell effector responses are down-regulated by inhibitory molecules like the SH2-containing inositol-5’-phosphatase SHIP1 and the SRC-family-kinase LYN. To identify further molecules involved in a negative regulatory signalosome, we screened for proteins showing the same pattern of tyrosine phosphorylation as SHIP1, which is tyrosine-phosphorylated strongest upon supra-optimal antigen stimulation. The low-affinity IgG receptor, FcγRIIB, was found to be most strongly phosphorylated under supra-optimal conditions. This phosphorylation is the consequence of passive, antigen/IgE-dependent and progressive co-localization of FcεRI and FcγRIIB, which is not dependent on IgG. Upon supra-optimal FcεRI cross-linking, FcγRIIB phosphorylation is executed by LYN and protected from dephosphorylation by SHIP1. Analysis of FcγRIIB-deficient bone marrow-derived mast cells revealed an ambiguous phenotype upon FcεRI cross-linking. Absence of FcγRIIB significantly diminished the level of SHIP1 phosphorylation and resulted in augmented Ca2+ mobilization. Though, degranulation and IL-6 production were not or only weakly enhanced, respectively. Altogether our data establish the LYN/FcγRIIB/SHIP1 signalosome in the context of FcεRI activation, particularly at supra-optimal antigen concentrations. The fact that SHIP1 tyrosine phosphorylation/activation not only depends on FcγRIIB, highlights the necessity for its tight backup control.